Effects of Working Hours and Workload on Work-Life Balance Via Stress - Merrie Nathania; Pramana Saputra; Karsim Karsim (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines how job demands (workload and working hours) influence the work-life balance of early-career Generation Z employees in Indonesia, focusing on the mediating role of work stress. Methodology/approach: UA quantitative survey was conducted with 212 Gen Z employees (6 months–5 years of experience) across various industries. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results/findings: Working hours did not directly affect work-life balance, possibly due to flexible arrangements or effective time management. In contrast, workload significantly disrupted work-life balance. Both working hours and workload increased work-related stress. Stress significantly mediated the relationship between job demands and work-life balance, showing that their negative impact occurs mainly through stress. Conclusion: Workload and working hours affect work-life balance indirectly through stress. Addressing workplace stress is crucial for sustaining employee well-being and long-term performance. Limitations: The study is limited by its modest sample size, reliance on self-reported survey data, and data collection within a specific timeframe, which may affect generalizability. Contribution: The study highlights stress as a key mediator of job demands and work-life balance among Gen Z employees in Indonesia. Findings provide insights for organizations, HR, and policymakers to improve workload management, reduce stress, and enhance well-being and productivity.